The Use of Spectroscopy Handheld Tools in Brain Tumor Surgery: Current Evidence and Techniques - Lakomkin, Nikita; Hadjipanayis, Constantinos G. (Frontiers in Surgery, 2019)
The fundamental principle in the operative treatment of brain tumors involves achieving maximal safe resection in order to improve postoperative outcomes. At present, challenges in visualizing microscopic disease and residual tumor remain an impediment to complete tumor removal. Spectroscopic tools have the theoretical advantage of accurate tissue identification, coupled with the potential for manual intraoperative adjustments to improve visualization of remaining tumor tissue that would otherwise be difficult to detect. The current evidence and techniques for handheld spectroscopic tools in surgical neuro-oncology are explored here.